ZIF-67 Incorporated Sodium Alginate/Polyvinyl Alcohol Composite Beads for Efficient Adsorptive Removal of Reactive Blue 19 from Aqueous Solution - Nguyen Thi Hong Nhung; Pham Thi Huynh Nhu; Hoang Ai Le Pham; Thi Hong Anh Nguyen (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
In this study, ZIF-67/SA/PVA composite beads were synthesized and used to remove Reactive Blue 19 (RB19) from aqueous solution. The composites were prepared by integrating cobalt-based ZIF-67 into a sodium alginate/polyvinyl alcohol matrix with different SA/PVA ratios. The physicochemical properties of the composites were characterized by FT-IR, XRD, SEM–EDS, BET, TG, and pHpzc analyses. Among the investigated samples, ZIF-67/SA/PVA-1:3 exhibited the highest RB19 removal efficiency (96.45%). The removal efficiency increased with increasing adsorbent dosage and temperature, but decreased at higher RB19 concentrations. The pH-dependent adsorption behavior was consistent with the pHpzc of 7.77. The negative ΔG° values (−5.308 to −7.298 kJ.mol-1) and the positive ΔH° value of 15.297 kJ.mol-1 indicated that the adsorption process was spontaneous and endothermic. The equilibrium data fitted the Langmuir model better than the Freundlich model. These findings demonstrate the potential of ZIF-67/SA/PVA as a composite adsorbent for removing reactive dyes from contaminated water. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).